The effects of online tourism information quality on conative destination image: The mediating role of resonance - Wang, Xueyi; Wang, Xin; Lai, Ivan Ka Wai (Frontiers in Psychology, 2023)
With the increasing popularity of mobile applications, people enjoy browsing online tourism information on social media. This information may cause psychological resonance, which in turn stimulates travel intentions. This study examined the relationship between online travel information quality (OTIQ), resonance, and conative destination image. A partial least squares structural equation model was used to analyze the survey data of 426 users who recently used social media to browse online tourism information. The results show that four dimensions of OTIQ (value-added, relevancy, completeness, and design) affect cognitive resonance, and three dimensions of OTIQ (interestingness, design, and amount of information) affect emotional resonance. Both cognitive resonance and emotional resonance directly affect the conative destination image. This study complements the relevant knowledge of resonance theory and increases the application of resonance theory in the field of tourism. This study contributes to tourism research in psychology by revealing the process of conative destination image formation from OTIQ and resonance. It contributes to online tourism marketing research by identifying the factors of OTIQ that rise tourists’ resonance, thereby prompting them to generate a conative destination image. Understanding this mechanism helps destinations improve the quality of online tourism information to attract potential social media users to become destination tourists. It also provides recommendations to destination marketers to formulate appropriate marketing strategies in the age of innovative technology.